The relationship of mental ability, personality factors, teaching attitudes and efficiency ratings of elementary school teachers in one of the districts in the province of Cebu - Laping, Jose A. 1945-
This study involved 129 teachers in 8 elementary and 2 primary schools. The 16-Personality Factor Questionnaire showed that majority of the teachers are either "Below Average" or "Dull" in the quantitative area, linguistics, and general intelligence. They scored "Above Average" in sociability, emotional maturity, suspiciousness, and self-discipline. Majority showed negative attitudes towards teaching as a profession as gauged by the Minnesota Teacher Attitude Inventory. There is a relationship between mental ability and efficiency ratings but none between mental ability and teaching attitude.